MONITORING AND EVALUATION OF THE TAX VOLUNTEER PROGRAM FOR THE COUNTRY IN SUPPORTING THE DIGITAL TRANSFORMATION OF TAX ADMINISTRATION - Nathan Al Difari; Abdal (CV Naskah Aceh, 2026)
The Tax Volunteer Program for the Nation (RENJANI) is a strategic initiative of the Directorate General of Taxes (DGT) that utilizes trained university students as volunteer tax service agents . Amidst the acceleration of the digital transformation of Indonesian tax administration through the implementation of the Coretax system and the expansion of electronic services , RENJANI serves as a bridge between taxpayers and the ever- changing tax system . This study aims to analyze the effectiveness of the RENJANI program, identify obstacles to its implementation , and explain its contribution to the digital transformation of taxation and public services . Using a qualitative approach with a systematic document study method , data were obtained from tax regulations , official DGT reports , academic publications , and relevant public policy documents for the 2019–2023 period . The analysis was conducted through source triangulation and the CIPP (Context, Input, Process, Product) evaluation framework . The results show that RENJANI has contributed significantly to increasing tax compliance and literacy , with the number of taxpayers served increasing from 23,450 (2019) to 78,340 (2023), and the service satisfaction index reaching 86.1%. However , this program faces obstacles . Structural challenges include digital infrastructure disparities in the 3T ( frontier and remote) regions , variations in volunteer capacity , and rigid institutional coordination . The novelty of this research lies in the comprehensive application of the CIPP evaluation framework to university- based volunteer programs in the context of the digitalization of Indonesian public administration . Policy implications include the need for standardization of training modules , strengthening cross- sector coordination protocols , and integrating RENJANI into the digital tax governance ecosystem .